Nano-phytoremediation technologies for groundwater contaminates emerging research and opportunities - Chaudhary, Khushboo 1989-; Khan, Suphiya 1976-; Saraswat, Pankaj Kumar 1976- (IGI Global, 2020)
"This book explores phytoremediation and some experimental methods used in life science laboratories. It also examines various heavy metals and non-metals and their effect on remedial approaches"--